Operasi Cross-Union pada Koleksi Himpunan Koteri Majority - Arsal, Armayani; Ningsih, Setia (Scimadly Publishing, 2022)
Coterie is a collection of sets called quorum which satisfies that any two sets have a non-empty intersection and are not property contained in one another. Based on topology, there are many types of coterie, for example, majority coterie. The majority coterie is a type of coterie with more availability than others to solve the problem of a distributed system. There are two types of majority coterie, dominated and non-dominated. The coterie join algorithm is an easy way to construct a new coterie with sizes larger quorum. In this study, we define a union operation for a majority coterie, called a cross-union operation. Then we prove that by using this algorithm, a new coterie is non-dominated if and only if the initial coteries are non-dominated.